Feed intake, emission of enteric methane and estimates, feed efficiency, and ingestive behavior in buffaloes supplemented with palm kernel cake in the Amazon biome - Amaral Júnior, João Maria do; Martorano, Lucieta Guerreiro; Nahúm, Benjamim de Souza; de Castro, Vinícius Costa Gomes; Sousa, Luciano Fernandes; Rodrigues, Thomaz Cyro Guimarães de Carvalho; da Silva, Jamile Andréa Rodrigues; da Costa Silva, Artur Luiz; Lourenço Júnior, José de Brito; Berndt, Alexandre; e Silva, André Guimarães Maciele (Frontiers in Veterinary Science, 2022)
The objective was to evaluate, in two different experiments, the effects of palm kernel pie supplementation on voluntary about consumption, in vivo production of methane and equivalents, feed efficiency and ingestive behavior in buffaloes in the Amazon biome. In experiment 1, to evaluate consumption, methane production and feed efficiency, 20 crossbred females, dry and empty, with a mean age of 34 months and initial body weight of 514 ± 69 kg were used, supplemented with palm kernel pie for 60 days. The supply was calculated in relation to body weight (BW) in four treatments: 0% (control); 0.25%; 0.50% and 1% of palm kernel cake, distributed in a completely randomized design. In experiment 2, to evaluate the ingestive behavior, 24 mixed-breed, dry and non-pregnant buffaloes, supplemented with palm kernel cake, were evaluated in the less rainy season (LR) and the wettest season (WS) of the eastern Amazon, distributed in a completely randomized in the same treatments of experiment 1. The offer of palm kernel pie in the supplementation increased the consumption of dry matter and components, reduced the production of enteric methane, the ratio per kg of meat produced and feed efficiency, and influenced the ingestive behavior (time grazing, rumination and idle) during the day.